O processo de planejamento estratégico territorial (pet): análise da Plataforma Ceará 2050 - Nascimento, José Welliton Silva do (2019)
Strategic Territorial Planning (PET) is a management tool for addressing changes in urban and rural areas in a consensual manner, based on the participation of key local actors - governments, the private sector and society (RUANO, 2019). The present study aims to propose guidelines for the PET process in the Ceará 2050 Platform. To this end, a qualitative research with exploratory and descriptive objectives was carried out through a case study; through semi-structured interviews with 4 Ceará 2050 project coordinators and 4 government staff members who oversee the coordinators. Data were processed through content analysis and operationalized in Atlas.TI 8 software. As a result, three stages of the STP process were identified: (1) Territory analysis; (2) territorial planning; and (3) Territorial governance. Finally, it was found that the implementation process of the Ceará 2050 Plan follows all the steps proposed in the literature and other strategic plans. The results also propose 4 guidelines for PET: 1) The territory should be understood as a strategic element of planning, supporting decision making; 2) Territorial planning is essential for development and proper planning in the impacted territories; 3) Establishing governance with full social participation is essential to the planning processes and 4) Following the other guidelines provides territorial development. In addition, it was possible to verify in the interviews words and excerpts that also refer and validate the research findings.